2007
DOI: 10.3311/pp.ci.2007-1.05
|View full text |Cite
|
Sign up to set email alerts
|

Near surface mounted FRP reinforcement for strengthening of concrete structures

Abstract: This paper is based on literature review regarding fibre reinforced polymers (FRP) used as near surface mounted (NSM) reinforcement for strengthening of concrete structures.Strengthening of structures is a complex task. Different systems can be used in order to utilize the fibre reinforced polymer in the most efficient way.Near surface mounted reinforcement is practical alternative to externally bounded reinforcement while it has many advantages.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
21
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(21 citation statements)
references
References 10 publications
(27 reference statements)
0
21
0
Order By: Relevance
“…Fiber reinforced polymer (FPR) strips and laminates are used as external bonded (EB) strengthening on the concrete surface of beams to improve their strength [6][7][8][9]. Another strengthening technique foresees near surface mounted (NSM) FRP rods with different shapes in grooves on concrete covers; many advantages of NSM technique seem to consider this an emerging technique [10][11][12][13] capable of improving the performance of RC with EB FRP. The assessment of strengthened RC beams both with EB FRP strips and with NSM FRP rods was experimentally investigated with vibration tests [14][15][16] analysis is commonly used to simulate the behavior of structural elements even if experimental data are fundamental for controlling theoretical models.…”
Section: Introductionmentioning
confidence: 99%
“…Fiber reinforced polymer (FPR) strips and laminates are used as external bonded (EB) strengthening on the concrete surface of beams to improve their strength [6][7][8][9]. Another strengthening technique foresees near surface mounted (NSM) FRP rods with different shapes in grooves on concrete covers; many advantages of NSM technique seem to consider this an emerging technique [10][11][12][13] capable of improving the performance of RC with EB FRP. The assessment of strengthened RC beams both with EB FRP strips and with NSM FRP rods was experimentally investigated with vibration tests [14][15][16] analysis is commonly used to simulate the behavior of structural elements even if experimental data are fundamental for controlling theoretical models.…”
Section: Introductionmentioning
confidence: 99%
“…The use of NSM in the rehabilitation and strengthening of existing damaged concrete structures has been becoming popular in the last decade [1][2][3][4][5]. Besides being simple and economical, this method also has a quick installation time.…”
Section: Introductionmentioning
confidence: 99%
“…Besides being simple and economical, this method also has a quick installation time. CFRP and GFRP bars are the most commonly used reinforcing materials for NSM [1][2][3][4]. However, the prices of FRP materials are still high compared to ordinary steel reinforcements and plates.…”
Section: Introductionmentioning
confidence: 99%
“…Surveys such as those reported in [8,16,17] showed that Carbon FRP (CFRP) has been used in most existing studies for NSM strengthening of concrete structures.…”
Section: Introductionmentioning
confidence: 99%